Critical Zone (CZ) Export to Streams as Indicator for CZ Structure and Function - Perdrial, Julia; Dere, Ashlee; West, Nicole; Sullivan, Pamela L. (Frontiers Media SA, 2020)
The goal of this Research Topic on streams as indicators for CZ structure and function is to explore linkages between biotic and abiotic weathering, soil biogeochemical processes, chemical and physical denudation and hydrology within the CZ. The CZ spans from the top of the vegetative canopy to the actively cycled groundwater providing life sustaining ecosystem services. However, rapid population growth and global climate change during the Anthropocene poses challenges to the Earth's CZ which is pushed to balance increased demand (e.g. crop yield) while maintaining the CZ's natural structure and other important ecosystem functions. Streams represent an integrator of many processes within the CZ and can thus carry the first signals of changing CZ health. As an important component of the CZ system, streams provide important information on hydrological, biogeochemical, and denudation fluxes, allowing a glimpse into the past, present and potential future of CZ function. The foci of recent stream water investigations include the role of catchment processes, riparian zone dynamics, hyporheic zone contributions and instream cycling to investigate nutrient dynamics, weathering and denudation, and hydrological partitioning. We now would like to expand this view conceptually to include the CZ.